Tożsamość pedagoga podejmującego dialog – dialog w edukacji jako praktyka budowania i utrwalania nowej rzeczywistości społecznej w nauczaniu - Windzberg Sasson , Ronit (Studia Edukacyjne, 2018)
One of the things that most influencethe professional identity in teaching is the professional training that the student teacher chooses. The professional training is built by educational pedagogy that supports the construction of the reality of the person who receives the training and contributes to it, and in this way, influenceshis professional identity. The dialogue between people is the way in which people influenceone another and help in the process of socialization. The dialogue influencesthe construction of the reality of people since the process of the construction necessitates at least two people in the process. The common denominator of socialization, social construction, and dialogue is the duality required from each one of the sides in these processes. The key to change is dialogic education. Dialogic pedagogy enables the participation in the construction of the educational reality in the 21st century.The article is composed of two parts. The firstpart presents a sociological infrastructure and asks the following questions: What is reality and how does the process of socialization and construction of a personal identity occur? The second part addresses the construction of the educational identity in the aspect of the educational ideology.